Survival and Success of an Apocryphal Childhood of Jesus: Reception of the Infancy Gospel of Thomas in the Middle Ages - Vukovic, Marijana (Studies of the Bible and its reception, 2022)
This book explores the transformations of the Infancy Gospel of Thomas in the Middle Ages. It also connects the different representations of children, childhood, everyday- and family life in the distinct textual versions to the ancient and medieval settings in which they appear. The text survived and influenced ideas and mentalities that shaped medieval minds in the East and the West, but also enhanced anti-Jewish sentiments